Ceftazidime-Avibactam Use in a Case Series of Difficult-to-Treat or Recurrent Infections in Pediatric Patients with Complex Chronic Conditions: Effectiveness and Absence of Resistance Development - Miguel García-Boyano; María Alós Díez; Lorena Fernández Tomé; Luis Escosa-García; Francisco Moreno Ramos; Cristina Schuffelmann-Gutiérrez; Emilio Cendejas Bueno; Cristina Calvo; Fernando Baquero-Artigao; Esteban Frauca Remacha (MDPI AG, 2024)
The prevalence of multidrug-resistant Gram-negative infections, particularly carbapenem-resistant strains, has become a significant global health concern. Ceftazidime-avibactam (CZA) has emerged as a promising treatment option. However, data on its efficacy and safety in children are scarce, necessitating further investigation. We conducted a descriptive case series at a tertiary hospital in Spain from February 2019 to January 2022. Pediatric patients (<16 years) treated with CZA for confirmed or suspected multidrug-resistant Gram-negative infections were included. The clinical and microbiological characteristics, treatment approaches, and outcomes were examined. Eighteen children received CZA treatment. All had complex chronic conditions, with the most frequent underlying main diseases being liver transplantation (n = 8) and biliary atresia (n = 4). The predominant type of infection for which they received CZA was intra-abdominal infection caused or suspected to be caused by OXA-48-producing Klebsiella pneumoniae. CZA was generally well tolerated. Within the first month of starting CZA therapy, two patients died, with one case directly linked to the infection's fatal outcome. Some patients needed repeated courses of therapy due to recurrent infections, yet no resistance development was noted. In summary, the use of CZA showed effectiveness and safety, while the lack of resistance development highlights CZA's potential as a primary treatment option against OXA-48-producing infections.